An effect of competition for food on the growth between red tilapia (Oreochromis sp.) and African catfish (Clarias gariepinus) - Muhamad Naqiuddin Mazeli.
Experiment were conducted to asses an effect of competition for food on the growth between red tilapia fry (Oreochromis sp.) and African catfish fry (Clarias gariepinus). Three treatment were tested using 3 replicate each means 9 aquarium where were stocked with red tilapia (30 g) and African catfish (25g). Each was stocked in ratio red tilapia: African catfish for 70%:30% in treatment 1 (Trt 1), 50%:50% for treatment 2 (Trt 2) and 30%:70% for treatment 3(Trt 3). Fish were fed with commercial diet food twice a day at 9.00 a.m and 4 p.m and fed at 5% of the body weight fish. A ANOVA was used to compare final weight gain, length of fish and the survival rate that have been collected in this experiment. From the observer and result, the oreochromis is more resistant to compete with African catfish because the survival rate show that no significant (P<0.05) on red tilapia than African catfish. More African catfish was found dead in the end of experiment. For length in all treatment of red tilapia was significantly higher daily gain than African catfish. For weight the tilapia only significantly different in treatment 1, for other treatment was no significantly different. It show that red tilapia was resistant in competition when it more dominance than African catfish.